2011
DOI: 10.1109/tit.2010.2090246
|View full text |Cite
|
Sign up to set email alerts
|

The Weights in MDS Codes

Abstract: The weights in MDS codes of length n and dimension k over the finite field GF(q) are studied. Up to some explicit exceptional cases, the MDS codes with parameters given by the MDS conjecture are shown to contain all k weights in the range n-k+1 to n. The proof uses the covering radius of the dual codeComment: 5 pages, submitted to IEEE Trans. IT. This version 2 is the revised version after the refereeing process. Accepted for publicatio

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…To connect and compare quantum error-correcting codes with classic error-correcting codes, we thenceforth denote a classic code that encodes k binary bits to n binary bits as an [n, k] code. Furthermore, we denote a quantum code that encodes k qubits to n qubits as an [26,27]. If a code has minimum distance d, it is capable of detecting any d − 1 and correcting any…”
Section: Theorem 1 If a Nice Error Basis ε Has Anmentioning
confidence: 99%
“…To connect and compare quantum error-correcting codes with classic error-correcting codes, we thenceforth denote a classic code that encodes k binary bits to n binary bits as an [n, k] code. Furthermore, we denote a quantum code that encodes k qubits to n qubits as an [26,27]. If a code has minimum distance d, it is capable of detecting any d − 1 and correcting any…”
Section: Theorem 1 If a Nice Error Basis ε Has Anmentioning
confidence: 99%
“…Let C be an [n, k, n − k + 1] q -MDS code. Ezerman et al [5] showed that C has a codeword u with wt(u) = n, except when either C is the dual of the binary repetition code of odd length n ≥ 3, or C is a simplex code with parameters [q + 1, 2, q] q . Hence, the following corollary can be derived.…”
Section: Aqmds Codes Of Lengthmentioning
confidence: 99%
“…Remark 1: When n = q+1, then the MDS codes in Proposition 1 are those codes given by Theorem 8 of [7]. When n < q + 1, they can be regarded as the codes are punctured from those codes given by Theorem 8 of [7].…”
Section: Punctured Mds Codesmentioning
confidence: 99%
“…In [7], [14], [24], some properties of MDS codes of length q +1 over the finite field F q were considered, where q is a prime power. In this paper, we consider those punctured MDS codes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation